Relationship between Religiosity and Emotional Maturity with Free Sex Behavior for Students of SMA Negeri Council of Lhokseumawe - Cindy Lola Yolanda; M. Abrar Parinduri; Nur'aini Nur'aini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the relationship between religiosity and emotional maturity with free sex behavior in SMA Negeri "X" Lhokseumawe students. This research is a quantitative descriptive study with a correlational approach. The population of this research is the students of SMA Negeri "X" Lhokseumawe, totaling 255 students. Sampling using purposive sampling technique with a total of 140 students. Data analysis used multiple regression analysis techniques. The results of data analysis showed that there was a significant negative relationship between religiosity and free sex behavior, with a correlation coefficient of rX1Y = -0.473 with p = 0.000 (p < 0.01), meaning that the higher the religiosity of students, the lower their free sex behavior. The coefficient of determinant (r^2) = 0.224, which means that religiosity contributes to free sex behavior by 22.4%. Furthermore, there is a significant negative relationship on emotional maturity with free sex behavior, with a correlation coefficient of rX2Y = -0.522 with p = 0.000 (p < 0.01), meaning that the higher the emotional maturity possessed by students, the lower their free sex behavior. The coefficient of determinant (r^2) = 0.272, which means that emotional maturity contributes to free sex behavior by 27.2%. There is a relationship between religiosity and emotional maturity with free sex behavior, with a coefficient of F = 45.398 with p = 0.000 (p < 0.01). The magnitude of the correlation rX1,2Y = 0.631 with a determinant coefficient (r^2) = 0.399, which meansthat together religiosity and emotional maturity contribute to free sex behavior by 39.9% and by 60.1% students' free sex behavior is influenced by other factors.